2014
DOI: 10.1039/c4ce00345d
|View full text |Cite
|
Sign up to set email alerts
|

Probing halogen bonds with solid-state NMR spectroscopy: observation and interpretation of J(77Se,31P) coupling in halogen-bonded PSe⋯I motifs

Abstract: Intra-halogen bond J couplings measured via NMR spectroscopy and interpreted using natural localized molecular orbitals offer novel insights into this class of non-covalent interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 92 publications
2
95
0
Order By: Relevance
“…[51] The changes represent increases of 0.4 %t o1 .6 %f or 35 Cl, 2.3 % to 3.8 %f or 79/81 Br, and 2.9 %t o4 .0 %f or 127 I. Each nucleus has au nique Sternheimer antishielding factor [57,58] and quadrupole moment (Q[ 127 I] = À617 mb; Q[ 79 Br] = 308.7(2) mb); Q[ 81 Br] = 257.9(2) mb; Q[ 35 Cl] = À81.12 mb), [59] with the latter taken into account using Equation (1) and solving for V 33 .The substantial shifts in the resonance frequencies as ar esult of halogen bonding far exceed the possible variation due to temperature fluctuations.…”
Section: Angewandte Chemiesupporting
confidence: 92%
See 2 more Smart Citations
“…[51] The changes represent increases of 0.4 %t o1 .6 %f or 35 Cl, 2.3 % to 3.8 %f or 79/81 Br, and 2.9 %t o4 .0 %f or 127 I. Each nucleus has au nique Sternheimer antishielding factor [57,58] and quadrupole moment (Q[ 127 I] = À617 mb; Q[ 79 Br] = 308.7(2) mb); Q[ 81 Br] = 257.9(2) mb; Q[ 35 Cl] = À81.12 mb), [59] with the latter taken into account using Equation (1) and solving for V 33 .The substantial shifts in the resonance frequencies as ar esult of halogen bonding far exceed the possible variation due to temperature fluctuations.…”
Section: Angewandte Chemiesupporting
confidence: 92%
“…It has been shown that the CÀIb ond stretches upon halogen bonding,w ith the resulting changes in the vibrational frequencies being good identifiers of halogenbonded complexes. [30,33] Consequently,t he value of C Q ( 127 I) correlates with both the CÀIc ovalent-bond length and the halogen-bond distance. [30,33] Consequently,t he value of C Q ( 127 I) correlates with both the CÀIc ovalent-bond length and the halogen-bond distance.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…8). 29 Computed J( 77 Se, 31 P) values improve relative to experiment when the iodinated halogen bond acceptor is included in the structural model. Natural localized molecular orbital (NLMO) calculations indicate that contributions from the selenium lone pair orbital dominate both the magnitude and the observed trend in the coupling constants.…”
Section: Noncovalent Interactions: Halogen Bondsmentioning
confidence: 99%
“…The method we have developed, inspired by Darren Brouwer's approach to solving zeolite structures using 29 Si (spin-1/2) NMR data, 21 begins with a structural model obtained from either a powder X-ray pattern or an ab initio approach. The model is refined successively against the experimental quadrupolar coupling data by evaluating the agreement between these data and those computed on the basis of the current structural iteration.…”
Section: Materials Characterization and Nmr Crystallographymentioning
confidence: 99%